Expansion Paths of the Telecommunications Companies under Globalisation. Telefónica and China Netcom Cooperation at the Beginning of the 21th Century (Global Journal of Human-Social Science, 2023)
This research addresses the paths taken by the telecommunications companies in their expansion under the globalisation during the first years of the new millennium The research adopts a firm level perspective with a Europe based multinational - Telef nica- and a state owned Chinese company -China Netcom- as actors The key issue is to determine the pattern of expansion selected by the partners and to elucidate the reasons of the choice The study is based on diverse sources such as reports of the companies studies of major institutions and international press The text is organized in three main sections namely the conversion of Asia into a target for the multinational the corporate alliances and the globalisation and the telecommunications in China and the entry Telef nica in China The research discloses as a pattern of expansion the collaboration by means of a blended approach of stake acquisition and contribution of knowledge and skill
Keywords: europe-china cooperation; china netcom; telefónica; globalisation; strategic alliances